Himālaya darśana - Bahuguṇā, Yogeśa Candra (Himālaya Darśana Prakāśana Samiti ; vitaraka Dūnaghāṭī Śikshaṇa Saṃsthāna, 1982)
Articles on the Himalaya region and its role in the Indian civilization, religion, and literature.